2018
DOI: 10.1155/2018/5980386
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Water Entry Problem of Pounders with Different Geometric Shapes and Drop Heights for Dynamic Compaction of the Seabed

Abstract: The water entry problem of three-dimensional pounders with different geometric shapes of cube, cylinder, sphere, pyramid, and cone was numerically simulated by the commercial software Abaqus, and the effects of pounder shape and drop height from the free surface of water on deepwater displacement and velocity as well as pinch-off time and depth were investigated. An explicit dynamic analysis method was employed to model fluid-structure interactions using a Coupled Eulerian-Lagrangian (CEL) formulation. The sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The four input parameters for Us-Up EOS, according to Equation ( 5), were set as proposed in References [5,56,[58][59][60]; that, is c 0 = 1480 m/s, s f = 0, and Γ 0 = 0. While the Us-Up EOS is primarily used for shock simulations, studies from the literature proved its applicability (with herein reported input values) also for water-impact configurations under low-velocity collisions [61,62]. Finally, the material density was set as ρ 0 = 938 kg/m 3 .…”
Section: Sph Birdmentioning
confidence: 99%
“…The four input parameters for Us-Up EOS, according to Equation ( 5), were set as proposed in References [5,56,[58][59][60]; that, is c 0 = 1480 m/s, s f = 0, and Γ 0 = 0. While the Us-Up EOS is primarily used for shock simulations, studies from the literature proved its applicability (with herein reported input values) also for water-impact configurations under low-velocity collisions [61,62]. Finally, the material density was set as ρ 0 = 938 kg/m 3 .…”
Section: Sph Birdmentioning
confidence: 99%
“…Besides these, the boundary element method, 26 constrained interpolation profile (CIP) method, 27 the arbitrary Lagrange–Euler (ALE) method, 28 , 29 and lattice Boltzmann method (LBM) 30 are all used for numerical simulation of water entry. Coupled Euler–Lagrange (CEL) analysis is another method to deal with the water entry problem, 31 , 32 which is effective and beneficial. Ahmadzadeh et al 33 adopted CEL method to simulate a free-falling sphere impacting the free surface of water.…”
Section: Introductionmentioning
confidence: 99%
“…In this article, based on the settings of CEL method, 31 34 with consideration of the influence of air content in water, an improved CEL method is proposed to simulate water entry of the cylinder. Besides, the water entry experiments of the cylinder are carried out.…”
Section: Introductionmentioning
confidence: 99%